Living in chains - Kannan Vijakumar (2018)
Living in Chains is a short documentary film that centers around the banned practice in Indonesia known as pasung. Pasung refers to the practice of physical restraint or confinement upon a person deemed as mentally ill. The documentary presents the standpoints of the traditional healers and the unconventional methods they employ to heal the patients. The film also serves to highlight the stigma and cultural beliefs that perpetuate the practice which still exists in certain parts of the world at this modern day and age.